Immunophenotype and differentiation capacity of bone marrow-derived mesenchymal stem cells from CBA/Ca, ICR and Balb/c mice - Ooi, Yin Yin; Rahmat, Zul'atfi; Jose, Shinsmon; Ramasamy, Rajesh; Vidyadaran, Sharmili (Baishideng Publishing Group, 2013)
AIM: To assess the capacity to isolate and expand mesenchymal stem cells (MSC) from bone marrow of CBA/Ca, ICR and Balb/c mice. METHODS: Bone marrow of tibia and femur were flushed, cultured and maintained in supplemented Dulbecco’s modified Eagle’s medium. MSC immunophenotype of cultures were tracked along increasing passages for positivity to CD106, Sca-1 and CD44 and negativity to CD45, CD11b and MHC class II. Differentiation capacity of MSC towards osteogenic and adipogenic lineages were also assessed. RESULTS: MSC were successfully cultured from bone marrow of all 3 strains, albeit differences in the temporal expression of certain surface antigens. Their differentiation into osteocytes and adipocytes were also observed. MSC from all 3 mouse strains demonstrated a shift from a haematopoietic phenotype (CD106-CD45+CD11b+Sca-1low) to typical MSC phenotype (CD106+CD45-CD11b-Sca-1high) with increasing passages. CONCLUSION: Information garnered assists us in the decision of selecting a mouse strain to generate MSC from for downstream experimentation.